Synergistic interaction between hydrophilic polyglycerol fatty acid esters and sucrose esters regulates fat crystallization at the water/oil interface in highly unsaturated whipped emulsions - Han, Wanjun; Deng, Yiqiu; Lin, Yiting; Zaaboul, Farah; Huangfu, Qiuling; Sun, Yanwen; Chai, Xiuhang; Tan, Chin Ping; Liu, Yuanfa (Elsevier B.V., 2025)
Interfacial crystallization is critical for stabilizing highly unsaturated whipped emulsions, but conventional emulsifier-mediated crystallization often yields poorly controlled microstructure and insufficient mechanical strength. This study developed a synergistic emulsifier strategy to precisely direct the interfacial crystallization of palm stearin (POS) using hydrophilic polyglycerol fatty acid ester (M-7D) and sucrose ester (P170). This approach effectively regulated crystallization kinetics and crystal morphology, leading to a remarkably stable crystalline network at the oil-water interface. Experimental results demonstrated that the M-7D/P170 combination significantly enhances nucleation behavior, reducing induction time by 75 % and increasing crystallization rate by 2.2 times. At an optimal 1:1 mass ratio, the system promoted the formation of stable β-form crystals, yielding a denser network characterized by a 27 % reduction in crystal thickness, an 18 % increase in crystal domain size, and a 10 % improvement in homogeneity. The synergistic effect between emulsifiers elevated the dimensionless parameter Na × Ja (nucleation number × nucleation rate) at the interface by 2–3 orders of magnitude. This enhancement facilitated the formation of continuous ring-like crystalline domains, which in turn promoted partial coalescence. Mechanistic insight from molecular simulations indicated that M-7D promoted the aggregation of P170's head groups, driving its aqueous partitioning and interfacial accumulation. This molecular reorganization directed POS crystallization into a denser, thinner layer, minimizing interfacial free energy. Consequently, the optimized interfacial architecture enabled the stabilization of aerated emulsions with only 5 % fat content. This work provides a fundamental understanding of emulsifier-mediated interfacial crystallization and presents a scalable, principles-guided strategy for designing high-performance, low-fat aerated products.